GE_GERICHTE P/3469/2020 vom 23. Juni 2021 - GE Cour de justice (2021)
CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE);PRINCIPE DE L'ACCUSATION;INDEMNITÉ(EN GÉNÉRAL) | LCR.90.al1; CPP.9; CPP.325; CPP.344; CPP.350; CPP.426.al1; CPP.426.al2; CPP.430; CPP.429; LCR.33; OCR.6